Nuevos enfoques y métodos en la historiografía sobre las independencias: el debate continúa - Juan B. Amores Carredano (Historia y Sociedad, 2011)
The complex process of independence of Latin American countries, whose bicentennial is celebrated at this time, has gained enormous prominence historiography in the last twenty years, driven largely by the proposed interpretation of the new political history of French origin. The abundant and rich production on this subject has left completely clear that this is one of the most relevant processes of the beginning of modern history, because it includes the whole process of the breakup of the Spanish monarchy and the birth of the Latin American countries in the other broader process of revolutions of the Atlantic World, reflecting the beginning of the end of the old regime in the West. This paper offers an interpretive framework on the latest trends and patterns of analysis of the various processes that occur in the Latin American independence.